Model-driven development of durable and scalable thermal energy storage materials for buildings. (15th February 2023) - Cui, Shuang; Kishore, Ravi Anant; Kolari, Pranvera; Zheng, Qiye; Kaur, Sumanjeet; Vidal, Judith; Jackson, Roderick
Abstract: The energy impact of integrating phase change materials (PCMs) in buildings for thermal energy storage has been modeled by various whole-building simulation programs, demonstrating that PCM incorporation can reduce energy consumption, provide grid flexibility and resilience, and reduce CO2 emissions. The models assume that the PCMs are in perfect operating condition and underestimate the impact of actual phase change behavior (e.g., enthalpy curve shape) on thermal load shifting in practical deployment. In this paper, we bridge the gap between theory and practice when evaluating the energy impact of PCMs by using a model-driven approach to develop durable thermal energy storage materials with desired phase change properties. For ease of integration, we fabricate shape-stabilized PCMs (ss-PCMs) by encapsulating solid-liquid polyethylene glycol (PEG) consisting of different molecular weights within mesoporous magnesium oxide (MgO) matrices. Learning from the modeling results, we manipulate phase change properties such as peak melting temperature and temperature glide of PEG-MgO ss-PCMs during the synthesis process to achieve desired properties. As such, the energy density is maximized within the optimum operating temperature range, which is critical to boosting energy efficiency. Compared to a case with no PCM, a layer of PEG-MgO ss-PCM integrated into the wall provides a 50% reduction in the peak load and also exhibits a repeatable phase change behavior for up to 1000 thermal cycles without leakage, showing durability of this material. We also show that this lab-scale synthesis process is easy to be scaled up by 100 times for a demonstration of large-scale industrial production. The synthetic tunability of transition temperature of ss-PCMs also extends their applicability beyond buildings. Graphical abstract: A model-driven approach is developed to design shape-stabilized (ss) phase change materials (PCMs) with desired phase change properties for practical thermal energy storage (TES) applications by quantifying the thermal load shifting. Our model identifies that maximizing the effective enthalpy within the operating temperature zone of end-use cases is the key to boosting the energy benefit. With the guidance of the model, we deliver a durable ss-PCM with long-term stability over 1000 phase change cycles and demonstrate a large-scale (∼100X) production method. The developed ss-PCM shifts ∼50% thermal load during the peak period, suitable for TES in building envelopes and beyond. Image 1 Highlights: Utilized a model-driven approach to develop shape stabilized phase change materials. Provided guidance on how to tune phase change materials for maximized load shifting. Maximized the enthalpy within the operating temperature for energy efficiency. Showed durable thermal energy storage with 1000 repeatable phase change cycles. Demonstrated 100X scalable synthesis of shape-stabilized phase change materials.